Comparison of Two Different Canine Anti-IgG Antibodies for Assessment of Oligoclonal Bands in Cerebrospinal Fluid and Serum of Dogs via Isoelectric Focusing Followed by an Immunoblot - Prümmer, Julia K.; Stein, Veronika M.; Marti, Eliane; Ziegler, Mario; Lutterotti, Andreas; Jelcic, Ilijas; Steffen, Frank; Buch, Thorsten; Maiolini, Arianna (Frontiers in Veterinary Science, 2022)
Isoelectric focusing followed by immunoblotting is a method routinely used in human medicine to assess the presence of oligoclonal bands (OCBs) in cerebrospinal fluid (CSF) and serum. The detection of OCBs is a valuable diagnostic test, especially important in patients with the suspicion of multiple sclerosis (MS), in which at least two OCBs are found in the CSF not present in paired serum samples in up to 95 % of patients. So far, presence of OCBs in CSF and serum of dogs has only been investigated in a small cohort of dogs diagnosed with degenerative myelopathy and healthy dogs. The main objective of the current study was to describe the method used for OCB detection and compare two different canine anti-IgG antibodies: a canine rabbit-anti-IgG antibody (Jackson ImmunoResearch) versus a canine goat-anti-IgG antibody (Bio-Rad). The method was performed according to the instructions of the commercial kit used. The canine goat-anti-IgG antibody showed a better performance than the canine rabbit-anti-IgG antibody. The availability of the technique of OCB detection in the dog paves the way for further studies, especially in the field of inflammatory diseases of the canine central nervous system, and comparison between specific human and canine diseases.